(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
In a world of fierce competition companies of different activities strive to strengthen their competitiveness in order to be able to deliver greater value to their customers and gain a distinct sites in competition with other companies in the market at the local and international levels. Every company seeks to focus on one or more of the competitive capabilities in order to turn it into an obvious advantage or a number of competitive advantages to contribute in improving the performance and superiority over its competitors. Therefore, the management of companies no longer need only useful information for the internal aspects of the environment, but also need to include the external environment that includes various and constantly changing factors from competitors and customers alike. Accordingly, the research aims to verify the role of accounting information system in enhancing the competitiveness of public industrial companies, using data collected by questionnaires distributed to a sample of auditors at the public industrial sector’s auditing committees of the of Federal Supreme Audit Board. The research has reached a number of results, the most important is that the financial accounting information system provides useful information contributing to the rationalization of economic decision-making process for parties outside the company and the management accounting information system provides useful information contributing to the rationalization of the decisions of the Parties within the company. Also, that the accounting information system does not provide useful information about both the external and internal factors that contribute to enhancing the competitiveness of the company.